Immunosuppressors (CsA, MPA) and IVIg Act Directly Upon Endothelial Cells and Differentially Alter their Ability to Activate Allogeneic T-CD4+. (July 2018) - Lion, Julien; Burbach, Maren; Cross, Amy; Poussin, Karine; Kaveri, Srini; Glotz, Denis; Mooney, Nuala
Abstract : Introduction: The allograft endothelium of the donor forms an interface with recipient leukocytes and regulates the immune response. We have shown that microvascular endothelial cells (mECs) simultaneously induce expansion of FoxP3hiTreg and of Th17 (Taflin et al, PNAS 2011). Although the outcome of immunosuppression has been extensively studied in circulating leukocytes, the effect of immunosuppressors (IS) and of IVIg on the endothelium has not been examined. This study determined whether commonly used IS or IVIg alter the ability of mECs to activate inflammatory or regulatory CD4+-T responses. Methods: We investigated the effect of cyclosporine A (CsA), mycophenolic acid (MPA) and intravenous immunoglobulins (IVIg) singly, or in combination on the phenotype of mECs. Allogenicity of the mECs was examined in an experimental model of mECs interaction with allogeneic PBMC. Results: HLA-DR and CD54 expression are important for Treg expansion by mECs. Incubation with CsA, MPA or IVIg significantly increased CD54 expression in mECs. HLA-DR was strongly reduced by MPA and by high levels of CsA whereas IVIg increased expression in mECs. The production of IL-6 by mECs, which is crucial for Th17 expansion, was reduced by all IS tested. Immunogenicity of mECs was examined in co-cultures of mECs and PBMC. Either CsA or MPA pretreatment of mECs reduced their ability to expand Treg whereas pretreatment with IVIg increased amplification of Treg. IL-6 production in co-cultures was reduced with CsA or MPA. In order to better imitate the therapeutic use of IS, PBMC and mECs were both exposed to IS before co-culture. The effect of IS on the endothelial cell remained visible under these conditions. Finally, we tested combinations of CsA and IVIg, or MPA and IVIg, on the phenotype and function of mECs. Combining IVIg with MPA or CsA amplified the effect observed on CD54 expression and IL-6 secretion when they are used alone. Concerning HLA-DR expression, the combination of IVIg with MPA somewhat compensated the inhibition observed with MPA treatment alone. However, pretreatment of mECs with either CsA and IVIg or MPA and IVIg, did not alter IL-6 levels in co-cultures in comparison with CsA or MPA alone. Conclusion: Overall, this study reveals that the IS and IVIg have direct and distinct effects on mECs which skew their capacity to orient the CD4+T response. We have shown a drastic reduction of Treg by CsA and MPA. In contrast, treatment with IVIgs was associated with an increased pro-regulatory response. These data may reveal mechanisms which contribute to long-term effects of CsA and MPA and identify a hitherto unknown regulatory pathway of IVIg. AC is supported by the Société Française de Transplantation. CSL Behring have contributed to financing this study.